KAJIAN BEBERAPA DOSIS BOKASHI TANDAN KOSONG KELAPA SAWIT (TKKS) UNTUK MENGATASI KERACUNAN FE DAN PENGARUHNYA TERHADAP PRODUKSI PADI VARIETAS PAK TIWI - Benang Purwanto (Politeknik Pembangunan Pertanian Manokwari, 2016)
This study aimed : 1) determine the appropriate dose of fertilizer Bokashi treating poisoningFe; and 2) the effect of fertilizer application on rice yield TKKS Bokashi. This study wasconducted over four months from July to October 2015 Kampung Sumberboga Masni DistrictManokwari District. This study was an experimental study using single factor design with fourtreatment of multiple doses of Bokashi TKKS were arranged in a randomized block design(RBD) with three replications. The single factor is: B0 = Without using Bokashi TKKS; B1 = 1ton ha-1; B2 = 2 ton ha-1; and B3 = 3 tons ha-1. The results showed that: 1) The provision ofBokashi TKKS 3 ton-1 impact panicle length, grain junlah decline empty weight of 1000 seedsare better than other treatments; and 2) The Bokashi TKKS no significant effect on plant height,number of tillers per hill, and the number of filled grain. But give significantly different effecton panicle length, number of grains per panicle empty, and the weight of 1000 seeds.